Proposal of an inspection tool according to Nielsen s usability attributes [Propuesta de una herramienta de inspección según los atributos de usabilidad de Nielsen] (2020)
Usability has become a fundamental attribute for the development of interactive and competitive applications within the software industry, which allows software systems to fulfill the purpose for which they were created, as well as considering the types of users they are intended for. In order to determine if a software product is usable, Nielsen proposed a general set of quality attributes at the usability level (learnability, efficiency, memorability, errors and satisfaction). To evaluate the compliance of said attributes in a software system, in this paper we propose a set of criteria in terms of questions associated with each attribute and an inspection tool to verify compliance with these criteria. This tool aims to support the conduct of usability inspections at the academic level and within software development companies. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.